2006
DOI: 10.1152/ajpheart.00953.2005
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of epoxyeicosatrienoic acids on human endothelial cells from the pulmonary and coronary vasculature

Abstract: Protective effects of epoxyeicosatrienoic acids on human endothelial cells from the pulmonary and coronary vasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 57 publications
4
70
0
1
Order By: Relevance
“…Thus, GPR40 mediated gap junction disassembly by 11,12-EET would be expected to reduce apoptosis, promote cell growth and maintain barrier function. Consistent with this conclusion, EETs inhibit apoptosis and promote proliferation in ECs (15)(16)(17).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, GPR40 mediated gap junction disassembly by 11,12-EET would be expected to reduce apoptosis, promote cell growth and maintain barrier function. Consistent with this conclusion, EETs inhibit apoptosis and promote proliferation in ECs (15)(16)(17).…”
Section: Discussionsupporting
confidence: 75%
“…Additionally, 11,12-and 14,15-EETs inhibit smooth muscle cell migration and aromatase expression (8,9). On endothelial cells, 11,12-EET promotes cell growth, decrease apoptosis, migration, tube formation and angiogenesis, increases tissue plasminogen activator (tPA) release, increases cyclooxygenase-2 (COX-2) expression and alters connexin-43 (Cx43) expression and gap junctions (10)(11)(12)(13)(14)(15)(16)(17). EET isomers also inhibit platelet adhesion to the endothelium, and 11,12-and 8,9-EETs inhibit inflammation by decreasing leukocyte adhesion to the endothelium (18,19).…”
mentioning
confidence: 99%
“…A recent finding in a renal proximal tubular epithelial cell line demonstrated that EETs inhibit apoptosis induced by serum withdrawal and etoposide (6,41). We have reported that EETs inhibit apoptosis induced by the engagement of the death receptor Fas or by serum withdrawal in human vascular endothelial cells cultured from the heart or lung (17,36). Hence, we were interested to see whether EETs have the same antiapoptotic effect in cardiomyocytes after I/R since myocardial cell death caused by apoptosis is a main feature of this condition.…”
mentioning
confidence: 75%
“…Cells (neonatal myocytes and HL-1 cells) were cultured in 60-mm dishes to 70% confluency and subjected to normoxia or H/R with or without pretreatment with EET as described in Treatment of Cells. The cells were washed with PBS and treated with FITC-labeled annexin V (0.2 g/ml) for 20 min at room temperature (17). Labeling with FITCcoupled annexin V was performed according to the manufacturer's protocol (BD Biosciences, San Diego, CA) as previously described (17).…”
Section: Annexin V Bindingmentioning
confidence: 99%
“…EETs and CYPs reportedly inhibit apoptosis induced by Fas ligand, 30 TNF-␣ induced, 31,32 serum deprivation, 30 etoposide, arachidonic acid, ceramide production, inhibition of reactive oxygen species, 33 and hypoxic reperfusion possibly by antagonizing reactive oxygen species. 34 Our data are also in agreement with a previous report that MAPK and PI3/Akt signaling pathways protect endothelial cells from TNF-␣ induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%